Sosialiasi Peningkatan Usaha UMKM Untuk Pemula Pada Pondok Pesantren Hidayatul Fatir, Kampung Ciherang RT.02, RW 04 Desa Maja, kabupaten Lebak, Provinsi Banten - Intan Arsitia Djafri; Dian Prilia; Lulu Febriany; Mahar Malindo; Mutia Takdir Purmana (LPPM Politeknik Piksi Ganesha, 2025)
This study aims to examine the role of socialization in improving micro, small, and medium enterprises (MSMEs) for beginners at Hidayatul Fatir Islamic Boarding School, Kampung Ciherang RT.02 RW 04, Maja Village, Lebak Regency, Banten Province. MSMEs play a strategic role in community economic development; however, beginner MSME actors often face various challenges, such as limited knowledge, low entrepreneurial motivation, and inadequate business management skills. This study employed a qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that MSME development socialization has a positive impact on increasing participants’ understanding of basic MSME concepts, simple business management, and marketing strategies. In addition, the socialization activities enhance participants’ motivation and self-confidence to start businesses based on local potential. Nevertheless, several obstacles were identified, including limited time for socialization activities and the need for continuous assistance. The study concludes that socialization is a strategic initial step in empowering beginner MSMEs in an Islamic boarding school setting and has the potential to support sustainable community economic development